The use of Laurus nobilis and Mentha pulegium essential oils against Sitophilus zeamais (Coleoptera: Curculionidae) on stored maize - Barros, Graça (2015)
Laboratory studies were carried out to evaluate the effects of some essential oils from Laurus nobilis and Mentha pulegium against Sitophilus zeamais on stored maize. The concentrated essential oils at different volumes of 0.5 μL, 1.5 μL, 2.5 μL, 5.0 μL and 10 μL, were poured on filter papers with 2 cm Ø each. For diluted oils, the fixed volume of 15 μL of different concentrations of 1:150v/v, 1:100 v/v, 1:75 v/v, 1:50 v/v and 1:10 v/v either in methanol or n-hexane were used to impregnate the filter papers. Treatments with the concentrated oils were more effective. All the concentrations used from M. pulegium provided 100% adult mortality and no progeny production were achieved. L. nobilis has revealed 100% adult mortality at 3.185 μL/cm2. Regarding the treatments with diluted oils once again the oil from M. pulegium provided 100% adult mortality at concentrations of 1:50 v/v and 1:10 v/v. L. nobilis was not effective at any of the concentrations used. There were no significant differences between the solvents used